God, Sexuality and the Self: An Essay ‘On the Trinity’ - Marnus, Havenga (Stellenbosch Theological Journal, 2016)
God, Sexuality and the Self: An Essay ‘On the Trinity’ by Coakley, Sarah 2013, Cambridge: Cambridge University Press ISBN: 9780521552288